The Role of Kinesthetic Reference Frames in Two-Handed Input Performance - Balakrishnan, Ravin; Hinckley, Ken (UIST '99 Proceedings of the 12th annual ACM symposium on User interface software and technology, 1999)
We present experimental work which explores how the match (or mismatch) between the input space of the hands and the output space of a graphical display influences two-handed input performance. During interaction with computers, a direct correspondence between the input and output spaces is often lacking. Not only are the hands disjoint from the display space, but the referenece frames of the hands may in fact be disjoint from one another if two separate input devices (e.g. two mice) are used for two-handed input. In general, we refer to the workspace and orgin within which the hands operate as kinesthetic reference frames. Our goal is to better understand how an interface designer's choice of kinesthetic reference frames influences a user's ability to coordinate two-handed movements, and to explore how the answer to this question may depend on the availability of visual feedback.